Students' Thinking Ability Predicted Through Questioning Skills - Yeni Nur Prilanita; Nenden Susilowati (Institut Agama Islam Negeri Jember, 2022)
The more experience a person has in learning or has more knowledge, the more complex the questions will be. Based on this, an individual's thinking ability influences questioning skills. This research aims to investigate the skills of asking questions related to thinking skills in the learning process in the classroom, which Bloom's taxonomy theory can explain. This research is associative explanatory research with a quantitative predictive approach. Analysis of research data uses regression analysis techniques. The study concludes that there is an influence between the thinking ability and the questioning skills of high school students.